Deleterious effects of phosphate on vascular and endothelial function via disruption to the nitric oxide pathway - Stevens, Kathryn K.; Denby, Laura; Patel, Rajan K.; Mark, Patrick B.; Kettlewell, Sarah; Smith, Godfrey L.; Clancy, Marc J.; Delles, Christian; Jardine, Alan G. (Nephrology, dialysis, transplantation, 2017)
Hyperphosphataemia is an independent risk factor for accelerated cardiovascular disease in chronic kidney disease (CKD), although the mechanism for this is poorly understood. We investigated the effects of sustained exposure to a high-phosphate environment on endothelial function in cellular and preclinical models, as well as in human subjects. Resistance vessels from rats and humans (± CKD) were incubated in a normal (1.18 mM) or high (2.5 mM) phosphate concentration solution and cells were cultured in normal- (0.5 mM) or high-phosphate (3 mM) concentration media. A single-blind crossover study was performed in healthy volunteers, receiving phosphate supplements or a phosphate binder (lanthanum), and endothelial function measured was by flow-mediated dilatation. Endothelium-dependent vasodilatation was impaired when resistance vessels were exposed to high phosphate; this could be reversed in the presence of a phosphodiesterase-5-inhibitor. Vessels from patients with CKD relaxed normally when incubated in normal-phosphate conditions, suggesting that the detrimental effects of phosphate may be reversible. Exposure to high-phosphate disrupted the whole nitric oxide pathway with reduced nitric oxide and cyclic guanosine monophosphate production and total and phospho endothelial nitric oxide synthase expression. In humans, endothelial function was reduced by chronic phosphate loading independent of serum phosphate, but was associated with higher urinary phosphate excretion and serum fibroblast growth factor 23. These directly detrimental effects of phosphate, independent of other factors in the uraemic environment, may explain the increased cardiovascular risk associated with phosphate in CKD.